[Wilhelm August Lehmann, 1870-1934] - Brockhagen, Marga (Fall;Foreign Language., 2000)
Keywords: dept.wll; faculty_collection; sabbatical_report

Second and Foreign Language Learning Through Classroom Interaction - Hall, Joan Kelly; Verplaetse, Lorrie Stoops (Erlbaum, 2000)
This volume brings together the current theoretical interest in reconceptualizing second and foreign language learning from a sociocultural perspective on language and learning, with practical concerns about second and foreign language pedagogy. It presents a set of studies whose focus is on the empirical description of particular practices constructed in classroom interaction that promote the learning of a second or foreign language. The authors examine in detail the processes by which the learning of additional languages is accomplished in the interaction of a variety of classrooms and in a
Keywords: Language and languages; Study and teaching; Interaction analysis in education; dept.wll; faculty_collection